Effects of glyphosate on soybean symbiotic microorganisms, in culture media and in greenhouse - Malty, Juliano dos Santos; Siqueira, José Oswaldo; Moreira, Fátima Maria de Souza (Pesquisa Agropecuaria Brasileira, 2006)
The effects of the Roundup herbicide on three strains of Bradyrhizobium elkanii (BR 29, INPA 80A and INPA 553A), one of B. japonicum (BR 86), and on three species of arbuscular mycorrhizal fungi (AMF) (Gigaspora margarita, Glomus etunicatum and Scutellospora heterogama), were evaluated in culture media containing increasing concentrations of the herbicide (0–454 µM); evaluations were also made on the effects on nodulation and mycorrhiza colonization of soybean grown in a soil treated with Roundup doses equivalent to 1.25 to 10 L ha-1 before sowing. The herbicide inhibited growth of Bradyrhizobium spp. and AMF in culture medium. These effects were directly related to increasing concentrations, and varied depending on the strain and species evaluated. However, in vitro inhibition occurred only when concentrations were greater than that recommended for use in the field. Strains BR 29, INPA 553A and INPA 80A showed to be more resistant to glyphosate, when compared to BR 86. Herbicide inhibition on germination and growth of AMF spore germ tubes decreased from G. etunicatum to S. heterogama and G. margarita. Soil application of Roundup before sowing up to a dose equivalent to 10 L ha-1 had no effect on nodulation and mycorrhiza colonization of soybean.
Keywords: symbiosis; mycorrhiza; Bradyrhizobium; nodulation